Effect of Rhizobium on Growth and Biomass Production of Rice (Bangladesh Journal of Microbiology, 2012)
To characterize twenty Rhizobium strains isolated from nodules of lentil, grasspea and chickpea, an experiment was conducted in the Soil Microbiology laboratory of the Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh. The isolates were tested for growth on Congo red Yeast Extract Mannitol (YEM) agar, peptone glucose agar, and YEM agar containing Bromothymol blue (BTB). All the strains except Ls 12 absorbed Congo red dye very weekly. Except Le 2 strains, isolated from lentil showed no growth in peptone glucose agar. All the strains isolated from grasspea and chickpea showed moderate growth on this   medium. All the strains were fast-growing and showed acidic reaction on YEM agar medium. Among the   strains isolated from lentil, Le 1, Le 2 and Le 4 produced moderate turbidity while Le 3, Le 6, Le 7 and Le 8   produced high turbidity in YEM broth. All the strains isolated from grasspea except Ls 3 and chickpea except   Ca 1 produced moderate turbidity in YEM broth medium. Strains Ls 3 and Ca 1 produced high turbidity. To   assess the effect of ten of these Rhizobium isolates viz. Le 1, Le 4, Le 6, Le 8, Ls 1, Ls 2, Ls 6, Ls 7, Ca 3 and Ca   4 on growth and biomass production of rice, a follow-up experiment was conducted in the same laboratory. Root length of rice was significantly increased over control (without inoculation) due to inoculation with different Rhizobium strains. The highest root length (9.63 cm) was obtained by inoculation with strain Ls 6   isolated from lentil. All the Rhizobium strains produced significantly higher shoot length, fresh and dry   biomass over control. The highest shoot length (16.50 cm), fresh biomass (138.3 mg) and dry biomass (27.75   mg) were also obtained from the strain Ls 6. DOI: http://dx.doi.org/10.3329/bjm.v28i2.11818 Bangladesh J Microbiol, Volume 28, Number 2, December 2011, pp 64-68